(untitled) (Research, Society and Development, 2021)
Extensive treatments can eventually be challenging. Even more so when the patient has limitations such as extensive tooth loss and skeletal changes, including overgrowth of the lower jaw. When indicated, these treatments tend to discourage patients due to the history of previous failures. Therefore, in addition to an interdisciplinary dental team composed of oral and maxillofacial surgeons, and prosthodontists, a nutrologist, a speech therapist, and a psychotherapist were involved in the treatment of this case. A 52-year-old female patient, Angle Class III malocclusion, with few teeth and extensive maxillary bone loss, attended the dental clinic of the Brazilian Association of Dentistry in Uberlândia. The treatment involved reverse planning, extraction of the dental remnants, calvarial bone grafting, placement of 6 titanium implants (Neodent) in the maxilla (upper jaw) and 5 in the mandible (lower jaw), orthognathic surgery, and installation of implant-supported fixed complete dentures in both jaws. Furthermore, psychotherapeutic and nutrologist’s interventions were necessary during the dental treatment, concluding the treatment with speech therapy. Within the limitations of this case, the multidisciplinary approach proved to be efficient. It promoted the reestablishment of the stomatognathic system functions without compromising nutrition during the periods when it was impossible to wear prostheses for better healing of the tissues.